2021
DOI: 10.1186/s12958-021-00842-w
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of miR-16, miR-let-7a and their target genes expression in human blastocysts following vitrification and re-vitrification

Abstract: Embryo cryopreservation is a widely used technique in infertility management and today is an essential part of assisted reproductive technology (ART). In some cases, re-vitrification can be applied to good quality supernumerary warmed embryos that have not been transferred in the present cycle. However, there is no study about re-vitrification impact on microRNA and gene expression in human embryos. The purpose of this study is to evaluate miR-16, miR-let7a and target genes expression in in vitro produced huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In an attempt to explain an underlying mechanism, the authors argued that the cryopreservation procedures could have elicited transcriptional changes in the embryos enough to hinder their developmental competence in utero. With this regard, only one study has assessed and shown that re-vitrification can alter the RNA of human blastocysts ( Daneshvar et al , 2021 ). Similarly, Farhi and colleagues reported lower pregnancy rates after double cryopreservation (n = 25) with slow freezing at the cleavage and blastocyst stages compared with after single cryopreservation (n = 50) at blastocyst stage only ( Farhi et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to explain an underlying mechanism, the authors argued that the cryopreservation procedures could have elicited transcriptional changes in the embryos enough to hinder their developmental competence in utero. With this regard, only one study has assessed and shown that re-vitrification can alter the RNA of human blastocysts ( Daneshvar et al , 2021 ). Similarly, Farhi and colleagues reported lower pregnancy rates after double cryopreservation (n = 25) with slow freezing at the cleavage and blastocyst stages compared with after single cryopreservation (n = 50) at blastocyst stage only ( Farhi et al , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a family of miRNAs termed CryoMiRs have been shown to be associated with freezing tolerance, and regulate metabolism in mammalian hibernators and insects ( Lyons et al, 2013 ; Singh and Storey, 2021 ). Finally, changes in miRNA expressions have been identified in cryopreserved oocytes, embryos and spermatozoa compared to fresh counterparts in human ( Daneshvar et al, 2021 ), mouse ( Heidari et al, 2019 ; Li et al, 2019 ; Movahed et al, 2019 ; Daneshvar et al, 2021 ; Xu et al, 2021 ), cow ( Shangguan et al, 2020 ) and pig ( Zhang et al, 2017 ; Dai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%